Oliver Twist - Dickens, Charles (Puffin Classics)
After orphan Oliver Twist asks for more food, he has to flee the workhouse and ends up on the streets of London. There he meets the Artful Dodger, who leads him to Fagin and his gang of pickpockets. When a thieving mission goes wrong, Oliver narrowly avoids prison and finds himself in the care of kind Mr. Brownlow. But Fagin and the brutal Bill Sikes go in search of the young orphan, determined to drag him back